2017
DOI: 10.1002/etc.4016
|View full text |Cite
|
Sign up to set email alerts
|

Vitellogenin concentrations in feral Danish brown trout have decreased: An effect of improved sewage treatment in rural areas?

Abstract: Feminization of male and juvenile fish because of exposure to estrogens or estrogenic chemicals in effluents from central wastewater treatment plants (WWTPs) is a worldwide issue of concern. Intersex and induction of the female yolk protein, vitellogenin, in male and juvenile fish are robust biomarkers for estrogenic exposure, and feminized fish have been observed downstream of WWTP outlets in many countries. Danish central WWTPs reduce effluent estrogenicity effectively by advanced sewage treatment, and femin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…By quantifying estrogenicity of WWTP samples before and aer the treatment, it was possible to evaluate the water quality status aer treatment which translated to the effectiveness of the novel eco-friendly method and the WWTP respectively in wastewater treatment. In the same way, Giebner et al 78 quantied VTG levels in juvenile brown trout over two periods, between 2000 through 2004 and 2010 through 2016 to determine trend of chemical pollution in the river body. It was found that average VTG levels in the shes between 2000 and 2004 was signicantly higher than the quantied level between 2010 and 2016.…”
Section: Application Of Effect-based Monitoring Assays In Assessing Chemical Pollution and Water Qualitymentioning
confidence: 98%
See 1 more Smart Citation
“…By quantifying estrogenicity of WWTP samples before and aer the treatment, it was possible to evaluate the water quality status aer treatment which translated to the effectiveness of the novel eco-friendly method and the WWTP respectively in wastewater treatment. In the same way, Giebner et al 78 quantied VTG levels in juvenile brown trout over two periods, between 2000 through 2004 and 2010 through 2016 to determine trend of chemical pollution in the river body. It was found that average VTG levels in the shes between 2000 and 2004 was signicantly higher than the quantied level between 2010 and 2016.…”
Section: Application Of Effect-based Monitoring Assays In Assessing Chemical Pollution and Water Qualitymentioning
confidence: 98%
“…VTG secretion, unique to female sh species, has been widely used in different studies as a marker of feminisation in different male sh species due to estrogenic inuence of contaminants in water bodies. 78,85,[125][126][127][128][129][130][131][132][133] Assessment of VTG expression is oen used in conjunction with other estrogenicity bioassays as a complementary method for assessment of endocrine disruption within aquatic fauna. Such application was employed by Geraudie et al (2017) and Ganser et al (2019) in their studies where YES assay was used to evaluate estogenicity of water samples in addition to the VTG assay.…”
Section: Detected Estrogenic Activity In All Matricesmentioning
confidence: 99%
“…It is difficult to reconcile these observations, but we cannot exclude other potential sources of upstream estrogenic contamination and our findings here are not unprecedented. For example, studies in rural Denmark suggested that environmental estrogens derive from domestic sewage treatment facility, such as septic tanks, after observing elevated plasma VTG in caged brown trout (Salmo trutta). , Furthermore, high-density livestock farming and the use of animal manures and sewage sludge on farmland can also be a diffuse source of estrogens entering surface waters (e.g., refs and ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, studies in rural Denmark suggested that environmental estrogens derive from domestic sewage treatment facility, such as septic tanks, after observing elevated plasma VTG in caged brown trout (Salmo trutta). 40,49 Furthermore, high-density livestock farming and the use of animal manures and sewage sludge on farmland can also be a diffuse source of estrogens entering surface waters (e.g., refs 50 and 51). Our findings suggest that there has been a reduction in environmental estrogenic exposure between the mid-1990s and the contemporary assessment.…”
Section: ■ Results and Discussionmentioning
confidence: 99%